The Comorbidity Burden of Hidradenitis Suppurativa in the United States: A Claims Data Analysis - Kimball, Alexandra B. (Dermatol Ther (Heidelb), 2018)
INTRODUCTION: Prior studies have reported that hidradenitis suppurativa (HS) is accompanied by a myriad of physical and mental conditions. However, given the small sample sizes and the limited number of pre-selected comorbidities, these studies do not provide a complete picture of the comorbidity burden of HS in the USA. Moreover, the relationship between HS severity and comorbidity burden has yet to be characterized. Using a large US claims database, we estimated the comorbidity burden associated with HS, stratified by disease severity. METHODS: A retrospective matched cohort design was used. Patients with HS were classified into two severity cohorts (milder and more severe) using an empirical algorithm based on treatments received. The comorbidity burden was compared between each HS cohort and their matched HS-free cohort, and between patients with milder vs. those with more severe forms of HS. RESULTS: Several physical and mental comorbidities were found to be more prevalent in both cohorts of patients with milder and more severe forms of HS than in their matched HS-free cohorts. The comorbidity burden also increased greatly as the disease progressed to more severe forms. CONCLUSIONS: The results of this study highlight the complexity of the comorbidity burden of HS patients and the need for a multidisciplinary approach to optimize the management of HS and its numerous associated comorbidities. FUNDING: AbbVie, Inc. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13555-018-0264-z) contains supplementary material, which is available to authorized users.